La radio informa y educa a los familiares de los adultos mayores con respecto a las necesidades socio-afectivas para el buen vivir, estudio de caso :Proyecto 60 y Piquito, programa Piloto - Calero Caviedes, María Belén (2013)
This thesis points out to investigate the socio-emotional needs of elderlypeople, that is reflected through a radio pilot program, which is going to inform and educate the family members of this focus group. To speak about a radio station as a tool to inform and educate, we can learn about the benefits offered by this medium. With several virtues, it captures the attention of different audiences and engage them in different scenarios and realities of life. To understand and learn from each other is an important mechanism for a reflective and critical society. The reality of the elderly people in Ecuador and the world is not encouraging. First world countries have somehow managed to sustain the issue of aging, as they have been subjected to lengthy processes with a superior political economy.What does not occur in Latin America and especially in our country. Our society is aging rapidly, and it is critical that we are not prepared in any way at all. Through this research we can raise awareness of the different needs of the elderly. Nobody can escape from old age and we all aim at the same place. It should be noted that this research proposal aims only citizen participation, the involvement of society in order to face a natural life cycle is aging and the idea that change is a problem, so one can raise community awareness and look at this stage as natural and normal, so one can age with dignity.